First historical cements in France from Boulogne sur Mer: Investigations on 19th century's manufactured cement‐based monuments. (21st November 2021) - Jebbawy, Marwa; Thiery, Vincent; Bouichou, Myriam; Marie‐Victoire, Elisabeth; Davy, Catherine; Izoret, Laurent; Albert‐Mercier, Cyrille; Moreau, Myriam
Abstract: The Boulogne‐Sur‐Mer area in the North of France is one of the cradles of the French cement industry (the other main one is Grenoble region due to Joseph Vicat's first cement works). From fast setting (Roman) to Portland, those cements were famous in France and have been used throughout the entire country. The main objective of this study is to give a preliminary insight of the type of binders used since there is currently few and scattered data on those specific structures and to assess the efficiency of traditional analytical techniques [X‐ray diffraction (XRD), optical (OM) and scanning electron microscopy (SEM) observations, coupled with EDS analysis] used to differentiate natural and artificial cements.